KEEFEKTIFAN PENGGUNAAN MEDIA AUDIO-VISUAL TERHADAP NILAI KOGNITIF SISWA MATERI CERITA DI SEKOLAH DASAR - Dwiki Ilmawan; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Universitas Tanjungpura, 2021)
AbstractThis study aims to examine the effectiveness of the use of audio-visual media onstudents' cognitive values compared to learning using conventional media on storymaterial for fifth grade students at SDN 34 South Pontianak. The method used inthis study is an experimental method with the form of research (Quasi experimentaldesign) is a type of research design that has a control group and an experimentalgroup selected randomly. This study used a population of 136 students and asample of 46 students. The data collection technique used in this study is ameasurement technique. The tools used to collect data are pretest-posttest testquestions. Based on the results of the research conducted, it showed an increasein students cognitive scores in identifying story elements in the experimental classusing audio-visual media with an average value of 90.00 compared to the controlclass using conventional methods with an average value of 84.26 and thecalculation of the effect size with a value of 1.856 with high criteria, theeffectiveness of the use of audio-visual media in identifying story elements onstudents cognitive values, thus tcount > ttable at a significance level of 5% withN=45 of 1.679 or 2.781 > 1.679. Based on these data, it can be concluded thatthere is an effectiveness of the use of audio-visual media on cognitive values in thefifth grade story material at the SDN 34 South Pontianak.Keywords: Effectiveness, Audio-visual Media, Cognitive Value